Assessing the Moderating Role of Organization Culture Effectiveness in Human Resource Management Practices and Organizational Innovation - Yusof, Ahmad Nizam Bin Mohd; Jamal, Hartini Zuhaila Binti (Journal of Entrepreneurship, Business and Economics, 2022)
The goal of this article is to investigate the role of human resource management (HRM) on innovation, organisational culture, and effectiveness. Firms' competitiveness and economic performance suffer when they are unable to expand and maintain their innovation capabilities. Malaysia's innovation capacity remains low. Furthermore, the lack of research and development (R&D) and innovation capabilities in the country shows significant hindrance. The ability of information and communications technology (ICT) enterprises to innovate is understudied despite the number of studies on the issue, specifically on ICT SMEs in Malaysia. Small and medium-sized enterprises (SMEs) in developing countries have received little attention in previous studies on Malaysian innovation because those studies have mostly focused on the manufacturing sector and include only large corporations from the West. A survey technique is applied to gather information from the owners, CEOs, and managers of ICT SMEs. This study plan to receive and evaluated 200 responses in total.  The research models and hypotheses were evaluated using the Partial Least Squares (PLS) method. This research addresses the gap between Human Resource Management and innovation The study's goal is to improve and evaluate a theoretical framework that connects HRM and inventive potential. The study's objective is also to enhance and test a theoretical framework linking HRM and innovative capability. This research addresses the gap between Innovative Centric Human Resource Management and innovation, as well as the connection between HRM and organization culture in the context of innovation. Research paper Keywords: HRM Practices; Innovation; Organizations Culture; Effectiveness Reference to this paper should be made as follows: Yusof, A. N. B. M., & Jamal, H. Z. B. (2022). Assessing the Moderating Role of Organization Culture Effectiveness in Human Resource Management Practices and Organizational Innovation. Journal of Entrepreneurship, Business and Economics , 10 (2), 127–138.